Anwuligan promotes the transition of the hair follicle cycle via the Wnt/β-catenin signaling pathway - Li, Fang; Zhang, Leyao; Li, Yan; Zheng, Xiang (Frontiers in Pharmacology, 2026)
BackgroundHair loss is a significant dermatological condition and hair regeneration depends on orderly cycle of hair follicle activity. Traditional Chinese Medicine (TCM) suggests that BaoHeWan can improve dry and sparse hair, but the molecular mechanisms behind this effect are not well known.MethodsThis study utilizes network pharmacology, phenotype observation, H&E staining, transcriptomics and molecular biology methods to investigate how anwuligan promote hair regeneration. demonstrated that anwuligan promoted hair regeneration in model mice.ResultsUsing network pharmacology analysis and molecular docking, anwuligan was found to be a major active ingredient in BaoHeWan, potentially acting by binding to CTNNB1. Transcriptomics analysis of mice treated with anwuligan, complemented by cellular validation, demonstrated that anwuligan induces upregulation of Ctnnb1 expression, activates the Wnt/β-catenin signaling pathway, promotes the proliferation of hair follicle stem cells (HFSCs), and facilitates the progression of the hair follicle cycle.ConclusionThese results elucidate the molecular mechanisms underlying anwuligan's facilitation of hair regeneration and offer a scientific foundation for the utilization of TCM in the treatment of hair loss.